Endoscopic management of pancreatic pseudocyst - Sharon, Wormi (International Surgery Journal, 2017)
Background: Pancreatic pseudocyst is a well-known complication of acute or chronic pancreatitis, with a higher incidence in the latter. It represents 80-90% of cystic lesions of the pancreas. Benign and malignant cystic neoplasms constitute 10-13%, congenital and retention cysts comprising the remainder. Diagnosis is accomplished most often by computed tomographic scanning, by endoscopic retrograde cholangiopancreatography, or by ultrasound, and a rapid progress in the improvement of diagnostic tools enables detection with high sensitivity and specificity. Endoscopic drainage provides a good alternative or supplement to a surgical treatment of pancreatic pseudocysts. Methods: This is a prospective study of 26 patients diagnosed to have Pancreatic Pseudocyst and treated by endoscopic drainage from 1st June 2008 to 30th September 2010 in St. John’s Medical College and Hospital, Bangalore. Transabdominal and endoscopic ultrasound, CT scan were used to determine the number, size, volume, wall thickness, location of pancreatic pseudocysts, the extent of pancreatic parenchymal disease, the nature of the main pancreatic duct and its relationship to the cyst, the presence of portal hypertension, venous occlusion, arterial anomalies and pseudoaneurysm. The indications for endoscopic drainage were symptomatic and/or bigger than 6 cm in major diameter pancreatic pseudocysts with a close opposition to the gastric or duodenal wall. Results: There were 26 patients with pancreatic pseudocyst and all of them are located in lesser sac. It mainly affects the middle-aged males with alcohol as the main etiology. Out of 26 patients 24 underwent endoscopic drainage and 2 patients were abandoned in view of vessel between the cyst wall and stomach which was picked up by EUS. Out of 26 patients, 5 developed infection which was proven by culture. Endoscopic cystogastrostomy was performed in 21 patients (80.8%), endoscopic cystogastrostomy with nasocystic drainage performed in 3 patients (11.5%), and abandoned in 2 patients. 2 patients developed bleeding, and managed conservatively. No intervention done. 5 patients underwent re-procedure (3 underwent nasocystic drainage, 1 aspiration, and the other cystogastrostomy), in view of recollection. Conclusions: Endoscopic drainage is safe and effective in experienced hand, less morbidity, cost effective, short hospital stay, can be repeated.